Variable Physical Drivers of Near‐Surface Turbulence in a Regulated River. Issue 11 (22nd November 2021) - Guseva, S.; Aurela, M.; Cortés, A.; Kivi, R.; Lotsari, E.; MacIntyre, S.; Mammarella, I.; Ojala, A.; Stepanenko, V.; Uotila, P.; Vähä, A.; Vesala, T.; et al.
Abstract: Inland waters, such as lakes, reservoirs and rivers, are important sources of climate forcing trace gases. A key parameter that regulates the gas exchange between water and the atmosphere is the gas transfer velocity, which itself is controlled by near‐surface turbulence in the water. While in lakes and reservoirs, near‐surface turbulence is mainly driven by atmospheric forcing, in shallow rivers and streams it is generated by bottom friction of gravity‐forced flow. Large rivers represent a transition between these two cases. Near‐surface turbulence has rarely been measured in rivers and the drivers of turbulence have not been quantified. We analyzed continuous measurements of flow velocity and quantified turbulence as the rate of dissipation of turbulent kinetic energy over the ice‐free season in a large regulated river in Northern Finland. Measured dissipation rates agreed with predictions from bulk parameters, including mean flow velocity, wind speed, surface heat flux, and with a one‐dimensional numerical turbulence model. Values ranged from ∼ 10 − 10 m 2 s − 3 to 10 − 5 m 2 s − 3 . Atmospheric forcing or gravity was the dominant driver of near‐surface turbulence for similar fraction of the time. Large variability in near‐surface dissipation rate occurred at diel time scales, when the flow velocity was strongly affected by downstream dam operation. By combining scaling relations for boundary‐layer turbulence at the river bed and at the air‐water interface, we derived a simple model for estimating the relative contributions of wind speed and bottom friction of river flow as a function of depth. Plain Language Summary: Inland water bodies such as lakes, reservoirs and rivers are an important source of climate forcing trace gases to the atmosphere. Gas exchange between water and the atmosphere is regulated by the gas transfer velocity and the concentration difference between the water surface and the atmosphere. The gas transfer velocity depends on near‐surface turbulence, but robust formulations have not been developed for river systems. Their surface area is sufficiently large for meteorological forcing to cause turbulence, as in lakes and reservoirs, but turbulence generated from bed and internal friction of gravity‐driven flows is also expected to contribute. Here we quantify near‐surface turbulence using data from continuous air and water side measurements conducted over the ice‐free season in a large subarctic regulated river in Finland. We find that turbulence, quantified as the dissipation rate of turbulent kinetic energy, is well described using equations for predicting turbulence from meteorological data for sufficiently high wind speeds whereas the contribution from bottom shear dominated at higher flow velocities. A one‐dimensional river model successfully captured these processes. We provide a fundamental model for estimating the relative contributions of atmospheric forcing and bottom friction as a function of depth. Key Points: Wind and river flow make comparable contributions to near‐surface turbulence in a regulated river Dissipation rates predicted from wind speed and flow velocity are in good agreement with observations Diel variability in dissipation rates occurs in response to flow regulation and atmospheric forcing